Chemical profiling, safety assessment, bioactive properties, and molecular interactions of the essential oil derived from Mentha pulegium L. - Rached, Sara; Habsaoui, Amar; Mzioud, Khaoula; Er-rajy, Mohammed; Abujaber, Feras; Imtara, Hamada; Oubihi, Asmaa; Haida, Sara; El-guourrami, Otman; Noman, Omar M.; Ourras, Samah; Tarayrah, Mahmoud; et al. (Frontiers in Sustainable Food Systems, 2025)
Mentha pulegium L., (MP) of the Lamiaceae family, endemic to Morocco, is a medicinal plant used in classical medicine. The aim of the present study is to enhance the value of this species by investigating the chemical composition of its essential oil (EO), antioxidant activity, toxicity, molecular docking and antimicrobial properties. In vitro measurement of antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) reduction assay and the 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid; ABTS) assay demonstrated the plant’s best performance. The toxicity test reveals that EO is non-toxic at an LD50 of 2000 mg/kg rat body weight. Evaluation of the in vitro antimicrobial effect by diffusion, direct contact, dilution and sporulation methods showed that all strains tested were sensitive to MP EO. Minimal inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values for clinical strains ranged from 2 mg/mL to 10 mg/mL. MP could therefore be a good alternative in the treatment of infectious diseases.